Comparative Analysis of Heat Transfer Coefficient for Wood and Non-wood Pulp Fiber: A Recent Study - G. Khan; S. N. Kazi; M. A. Syed; S. Nasar; A. Kakar (Advanced Aspects of Engineering Research Vol. 9, 2021)
The comparative study for obtained heat transfer coefficient for Acacia Mangium (wood) and Kenaf bast (non-wood) pulp fiber suspension were performed in a close loop circular pipe heat exchanger. During the test study it was observed that the magnitude of heat transfer coefficient strong influenced by the parameters including: fiber type, pulp concentration, characteristics as well as fiber pulping method. At a low fiber suspension concentration and higher flow rates, it was observed that higher values of heat transfer coefficient were achieved than that of water, in contrast, a decrease in heat transfer values were found at increasing concentration and lower pulp suspension. It was found that values of heat transfer coefficient decreases with increasing the fiber flexibility for both Acacia Mangium and Kenaf bast respectively. In the present research work, the fiber dimensions and fiber flexibility are inter-related along with values of heat transfer coefficient of both wood and non-wood fiber suspensions. By adopting proper fiber pulping processes, fiber quality can be improved by changing fiber pulp characteristics for the production of especial products.